Repeated Exercise Induces Release of Soluble P-Selectin in Patients with Intermittent Claudication - Kirkpatrick, U J; Mossa, M; Blann, A D; McCollum, C N (Thrombosis and Haemostasis, 1997)
Controversy exists as to whether exercise in patients with intermittent claudication causes a harmful biochemical effect associated with an ischaemia-reperfusion injury of skeletal muscle. We report on exercise-induced changes in neutrophil activation, soluble P-selectin and von Willebrand factor in 34 patients with intermittent claudication and 12 matched controls.Von Willebrand factor (vWF) showed a cyclical pattern of response to exercise in control subjects (rising from 103 ± 8 to 119 ± 7 U/dl); claudicants did not show this pattern but had higher levels of vWF throughout (p <0.03). There was no consistent pattern of response in neutrophil hydrogen peroxide production to exercise in either claudicants or control subjects. Soluble P-selectin levels increased after exercise, but this only reached statistical significance after repeated exercise in claudicants (rising from 320 ± 28 to 357 ± 28 ng/ml). This rise in soluble P-selectin after exercise may indicate progressive platelet activation which may contribute to the excess cardiovascular mortality that claudicants are prone to.